2021
DOI: 10.1002/dad2.12192
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of semantic intrusions to different etiological subtypes of MCI and cognitively healthy older adults

Abstract: Introduction: There is increasing evidence that susceptibility to proactive semantic interference (PSI) and the failure to recover from PSI (frPSI) as evidenced by intrusion errors may be early cognitive markers of both preclinical and prodromal Alzheimer's disease (AD). Methods: One hundred forty‐five participants were administered extensive clinical and neuropsychological evaluations including the Loewenstein‐Acevedo Scales for Semantic Interference and Learning (LASSI‐L), a sensitive cognitive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…Our paradigm also demonstrates that aMCIs are not per se more prone to semantic than to phonological intrusion errors but rather lose the benefit of semantic deeper processing, resulting in a comparable percentage of intrusion errors in both conditions (a profile similar to that obtained in recall and recognition). These results are in line with recent studies suggesting that the percentage of semantic intrusion errors related specifically to proactive interference on the LASSI-L (CRB1) is a clear marker to differentiate aMCIs from normally aging older adults (Capp et al, 2020; Kitaigorodsky et al, 2021), also shown to uniquely differentiate amyloid+ and amyloid− aMCI patients (D. A. Loewenstein et al, 2018) and even distinguish between those at-risk individuals with PreMCI who progressed to mild cognitive impairment over time from those who reverted to normal on longitudinal follow-up (E.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our paradigm also demonstrates that aMCIs are not per se more prone to semantic than to phonological intrusion errors but rather lose the benefit of semantic deeper processing, resulting in a comparable percentage of intrusion errors in both conditions (a profile similar to that obtained in recall and recognition). These results are in line with recent studies suggesting that the percentage of semantic intrusion errors related specifically to proactive interference on the LASSI-L (CRB1) is a clear marker to differentiate aMCIs from normally aging older adults (Capp et al, 2020; Kitaigorodsky et al, 2021), also shown to uniquely differentiate amyloid+ and amyloid− aMCI patients (D. A. Loewenstein et al, 2018) and even distinguish between those at-risk individuals with PreMCI who progressed to mild cognitive impairment over time from those who reverted to normal on longitudinal follow-up (E.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies using the LASSI-L have obtained equivocal results on the vulnerability of aMCI patients to semantic proactive interference, highlighting the need for further research (e.g., in their Spanish validation of the LASSI-L, Matías-Guiu et al, 2017). All in all, our results suggest that the analysis of errors committed due to PI would be a better marker of pathological cognitive change than the decrease in the number of words correctly recalled, a conclusion also raised in the literature (Gainotti et al, 2014; Kitaigorodsky et al, 2021; Torres et al, 2019).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Both the cue and the rest of the items are supposed to be represented by their own EPISODE module and none of them can become connected to the newborn granule cells if synaptogenesis is impaired. Finally, semantic interference should be a very good indicator of prodromal AD, as already evidenced by the excellent psychometric power of the LASSI-L test [ 56 , 57 ]. Our model provides a rationale for this observation: in the absence of successfully reinforced new associations, the subset of active granule neurons is expected to be defined by information encoded before the learning, and such information can already be at least partially semanticized.…”
Section: Resultsmentioning
confidence: 99%
“…The amyloid negative groups made the fewest number of LASSI-L semantic intrusion errors on Cued B2 (6.5% and 5.9%) followed by 23.7% of amyloid negative SNAP participants, and 40% of amyloid negative patients with other neurological conditions. In contrast, 75% of aMCI amyloid positive individuals (prodromal AD) made semantic intrusion errors on Cued B2 (Kitaigorodsky et al, 2021). Semantic intrusion errors did not differ in those who were predominant English-speakers as compared to Spanish-speakers.…”
Section: Psi Frpsi and Semantic Intrusion Errorsmentioning
confidence: 95%